Grid-edge renewable technologies enabling sustainable cities through big data analytics for energy sustainability - Bonatto, Benedito D.; Barbosa, Tiago M.; Costa, Vinicius B.F.; Freitas, Walmir; Silva, Luiz C.P.; Arioli, Fernanda C.T.; Ricciardi, Tiago R.; de Almeida, Madson C.; de Martino Jannuzzi, Gilberto; Castro, Marcelo S.; Guillardi, Hildo [UNESP] (Elsevier, 2025)
According to public data from the 2019 Distributor's Geographic Database (BDGD), the Brazilian public sector consumes 41.0 TWh of electricity per year, implying R$ 24.2 billion (US$ 4.8 billion) in expenses. The current business model is traditional, that is, the public sector exclusively purchases electricity from distribution companies at fixed rates. However, the electric sector business model has become outdated by the development of renewable distributed generation sources, energy storage systems, and competitive retail electricity markets. In this context of grid-edge technologies, where decarbonization, digitalization, and decentralization urgently promote energy transition, big data analytics applied to the BDGD can be useful for proposing more advanced business models for the public sector, focusing on enhancing electricity affordability, efficiency, and government sustainability. Therefore, this study contributes to an innovative framework called BDA4ES (Big Data Analytics for Energy Sustainability) by (i) creating a methodology that enables researchers to access the BDGD, process the data, and add complementary data, and (ii) conducting a thorough evaluation of investment opportunities in photovoltaic (PV) generation to make the Brazilian public sector more sustainable (financial, social, and environmental). Preliminary results demonstrate that by investing in PV generation, the Brazilian public sector could save R$ 476 billion (US$ 95 billion) over 25 years, representing a return on investment of 366 %, thus avoiding 46.2 Mt CO2-eq of global warming potential (GWP), representing 3.4 % per year of the annual Brazilian carbon footprint on electricity generation. Moreover, when assuming an interest rate of 4.4 % (2019 average Brazilian basic interest rate – SELIC) the discounted payback time is 6.3 years (again, between 1 and 2 political mandate of 4 years), and the Net Present Value (NPV) is R$ 233 billion (US$46.5 billion) over 25 years. From this perspective, considering the overall socieconomical, environmental and political benefits, it becomes evident the public sector energy sustainability project's potential. The conventional optimized tariff model (TAROT) indicates that such a project would imply regulatory tariff increases up to 2.52 %, which is not particularly worrisome. Therefore, the results demonstrate the economic, social, and environmental viability of deploying PV systems to supply green electricity to the public sector, thereby enabling sustainable cities. Although the analyses focused on the public sector and PV generation, the proposed methodology can be used to conduct several distinct studies on energy sustainability for corporate and government social responsibility.
Keywords: Corporate and government social responsibility; Data science; Economic viability; Energy transition; Grid edge technology; Photovoltaic systems; Public sector; Sustainability